Metamorfica Alice. L’originale di Lewis Carroll dalla stampa al digitale - Stefania Carioli (Studi sulla Formazione, 2017)
In the book apps considered in this essay, Alice in Wonderland has been animated and made interactive to offer an audience of young readers a literary masterpiece. I wonder if reading digital texts like this, that maintain the stylistic value of the original texts and that offer a playful insight into narrativity, can help young readers build a positive relationship with the literary classics.